NCR-sensitive gene expression and regulation of nitrogen interconversion by VID30 in Saccharomyces cerevisiae - Van der Merwe, George K., (George Karel)1968- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2002.